HPV8-E6 Interferes with Syntenin-2 Expression through Deregulation of Differentiation, Methylation and Phosphatidylinositide-Kinase Dependent Mechanisms - Marx, Benjamin; Miller-Lazic, Daliborka; Doorbar, John; Majewski, Slawomir; Hofmann, Kay; Hufbauer, Martin; Akgül, Baki (Frontiers in Microbiology, 2017)
The E6 oncoproteins of high-risk human papillomaviruses (HPV) of genus alpha contain a short peptide sequence at the carboxy-terminus, the PDZ binding domain, with which they interact with the corresponding PDZ domain of cellular proteins. Interestingly, E6 proteins from papillomaviruses of genus beta (betaPV) do not encode a comparable PDZ binding domain. Irrespective of this fact, we previously showed that the E6 protein of HPV8 (betaPV type) could circumvent this deficit by targeting the PDZ protein Syntenin-2 through transcriptional repression (Lazic et al., 2012). Despite its high binding affinity to phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2), very little is known about Syntenin-2. This study aimed to extend the knowledge on Syntenin-2 and how it its expression is controlled. We now identified that Syntenin-2 is expressed at high levels in differentiating and in lower amounts in keratinocytes cultured in serum-free media containing low calcium concentration. HPV8-E6 led to a further reduction of Syntenin-2 expression only in cells cultured in low calcium. In the skin of patients suffering from Epidermodysplasia verruciformis, who are predisposed to betaPV infection, Syntenin-2 was expressed in differentiating keratinocytes of non-lesional skin, but was absent in virus positive squamous tumors. Using 5-Aza-2’-deoxycytidine, which causes DNA demethylation, Syntenin-2 transcription was profoundly activated and fully restored in the absence and presence of HPV8-E6, implicating that E6 mediated repression of Syntenin-2 transcription is due to promoter hypermethylation. Since Syntenin-2 binds to PI(4,5)P2, we further tested whether the PI(4,5)P2 metabolic pathway might govern Syntenin-2 expression. PI(4,5)P2 is generated by the activity of phosphatidylinositol-4-phosphate-5-kinase type I (PIP5KI) or phosphatidylinositol-5-phosphate-4-kinase type II (PIP4KII) isoforms α, β and γ. Phosphatidylinositide kinases have recently been identified as regulators of gene transcription. Surprisingly, transfection of siRNAs directed against PIP5KI and PIP4KII resulted in higher Syntenin-2 expression with the highest effect mediated by siPIP5KIα. HPV8-E6 was able to counteract siPIP4KIIα, siPIP4KIIβ and siPIP5KIγ mediated Syntenin 2 re-expression but not siPIP5KIα. Finally, we identified Syntenin-2 as a key factor regulating siPIP5KIα expression. Collectively, our data demonstrates that Syntenin-2 is regulated through multiple mechanisms and that downregulation of Syntenin-2 expression may contribute to E6 mediated dedifferentiation of infected skin cells.